Pedagogies for employability: Understanding the needs of STEM students through a new approach to employability development - Bennett, Dawn; Knight, Elizabeth; Dockery, Michael; Bawa, Sherry (Taylor & Francis, 2020)
Labour market trends and the economic impacts of COVID-19 are elevating the importance of knowledge as a factor of production whilst concurrently eroding traditional forms of employment. Mindful of the implications for higher education, this study approached employability development as ‘the ability to find, create and sustain meaningful work across the career lifespan’. The study was grounded in social cognitive theory and adopted a metacognitive approach to employability. Data were generated through an online self-assessment completed by 12,576 students enrolled with Australian universities. Data from science, technology, engineering and mathematics (STEM) students were compared with those from students in non-STEM fields. STEM students differed in several key employability traits. The paper highlights the need to promote more nuanced occupational literacy about the future of work alongside awareness that STEM skills and capabilities are valued across multiple sectors and roles. Opportunities and challenges for embedding a pedagogy for employability are discussed.